A bim-oriented approach to the consistency of design and cost documentation in contemporary construction (Collection of scientific works «Scientific Problems of Architecture and Urban Planning» | ODABA, 2026)
The paper examines the problem of misalignment between design and costdocumentation as one of the key causes of cost overruns, schedule deviations, and reducedtransparency in construction project management. It is shown that conventional estimatingapproaches based on manual or semi automated quantity take off from drawings generate costdocumentation as an autonomous information product weakly connected to design data, which leadsto repeated recalculations of quantities and costs and to the accumulation of errors when designchanges occur. A BIM oriented approach using 5D BIM is substantiated, within which geometric,quantitative, and cost parameters are integrated into a single information model and maintained ascontrolled versioned data. The role of Quantity Take Off and Bill of Quantities processes isclarified, where QTO provides continuous extraction of quantitative indicators directly from modelelement parameters, while BOQ forms a structured document for cost calculations and contractualinteraction. It is demonstrated that the information model as a single reliable source of data enablesscenario based estimating, early comparison of alternative technical solutions, and promptassessment of the cost impact of design changes. The prerequisites for effective implementation of5D BIM in national practice are identified, including standardization of information requirements,classification systems, and change management in accordance with ISO 19650 principles. Theobtained findings may be applied in practice through the use of artificial intelligence tools withinBIM oriented cost management systems.